Global and Non-Global Solutions for Pseudo-Parabolic Equation with Singular Potential (Journal of Partial Differential Equations, 2025)
This paper considers initial boundary value to a pseudo-parabolic equation with singular potential $\frac{u_t}{|x|^s}-Δ u_t-Δ u =|u|^{p-2}u$ with $2